Teaching english as a foreign language major to gifted students - Phu Vu,; Lan Vu, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This study aims to outline the introduction of a special program for teaching the English language as a major (TEAM) to high school gifted students in Vietnam and how the students recognized its effectiveness. The data were collected via a survey and analyzed through descriptive statistics in order to categorize patterns of agreement and disagreement between two cohorts of gifted students. The results showed that the students’ initial expectations were met as the majority of them expressed satisfaction with the quality of the TEAM program at the school and appreciated its usefulness for their further study and career. The findings were interpreted in view of their implications for further development of this program as well as how to improve the quality of ELT from that experience.